PROFILE OF SCHOOL READINESS IN APPLYING STEM (SCIENCE, TECHNOLOGY, ENGINEERING, MATHEMATIC) EDUCATION - Yanti Herlanti; Usawatun Amalia; Ai Nurlaela (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2022)
STEM knowledge and skills are needed by students in order to survive in the era of the industrial revolution 4.0. This study aims to determine the level of readiness of public high schools in Bogor City in implementing STEM education. Descriptive research with survey method with stratified sample selection. The number of samples is three principals, nine science teachers, and 75 students. The research instrument was in the form of a questionnaire assessing readiness from aspects of the curriculum, supporting extracurriculars, admission selection, and STEM supporting facilities as well as students' interest in STEM. Data analysis uses a modified readiness score according to Aydin & Tascy (2005). The findings of the study show that public high schools in the city of Bogor are ready to implement STEM education. Readiness to apply STEM education is shown by the Principal. Students also showed readiness to apply STEM education, but needed a little improvement. As for the teacher, it shows unpreparedness and needs improvement.PROFIL KESIAPAN SEKOLAH SMA NEGERI KOTA BOGOR DALAM MENERAPKAN PENDIDIKAN STEM (SCIENCE, TECHNOLOGY, ENGINEERING, MATHEMATIC)AbstrakPengetahuan dan keterampilan STEM diperlukan peserta didik agar dapat bertahan pada era revolusi industry 4.0. Penelitian ini bertujuan untuk mengetahui tingkat kesiapan sekolah SMA Negeri di Kota Bogor dalam menerapkan pendidikan STEM. Penelitian deskriptif dengan metode survei dengan pemilihan sampel secara stratafikasi. Jumlah sampel adalah tiga orang kepala sekolah, sembilan orang guru Sains, dan 75 orang peserta didik. Instrumen penelitian berupa angket menilai kesiapan dari aspek kurikulum, ekstrakuler penunjang, seleksi masuk, dan fasilitas penunjang STEM serta minat peserta didik terhadap STEM. Analisis data menggunakan skor kesiapan menurut Aydin & Tascy (2005) yang telah dimodifikasi. Temuan penelitian menunjukan SMA Negeri di Kota Bogor siap menerapkan pendidikan STEM. Kesiapan penerapan pendidikan STEM ditunjukkan oleh Kepala Sekolah. Peserta didik pun menunjukkan kesiapan penerapan pendidikan STEM, namun perlu sedikit peningkatan. Adapun dari guru, menunjukkan ketidaksiapan dan perlu peningkatan.How To Cite: Yanti, H., Amalia, U., Nurlela, A. (2022). Profil Kesiapan Sekolah Sma Negeri Kota Bogor Dalam Menerapkan Pendidikan Stem (Science, Technology, Engineering, Mathematic). EDUSAINS, 14 (1) : 14-23.